2021
DOI: 10.1177/08912432211001297
|View full text |Cite
|
Sign up to set email alerts
|

Has the Economic Lockdown Following the Covid-19 Pandemic Changed the Gender Division of Labor in Israel?

Abstract: The economic shutdown and national lockdown following the outbreak of COVID-19 have increased demand for unpaid work at home, particularly among families with children, and reduced demand for paid work. Concurrently, the share of the workforce that has relocated its workplace to home has also increased. In this article, we examine the consequences of these processes for the allocation of time among paid work, housework, and care work for men and women in Israel. Using data on 2,027 Israeli adults whom we follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 18 publications
2
45
0
1
Order By: Relevance
“…Adams-Prassl et al ( 2020) used international survey data and found significant differences in job loss rates by gender in the United States and the United Kingdom, but not in Germany. Some studies found women -in particular mothers with young children -were more likely to reduce their working hours in the pandemic compared to men (e.g., Hupkau Yaish et al 2021 for Israel). Our study found some evidence which points at a potential further spread of part-time work among mothers as a consequence of the pandemic also in Austria (i.e., in case mothers who were in STW in 2021 re-enter regular employment on a part-time basis).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Adams-Prassl et al ( 2020) used international survey data and found significant differences in job loss rates by gender in the United States and the United Kingdom, but not in Germany. Some studies found women -in particular mothers with young children -were more likely to reduce their working hours in the pandemic compared to men (e.g., Hupkau Yaish et al 2021 for Israel). Our study found some evidence which points at a potential further spread of part-time work among mothers as a consequence of the pandemic also in Austria (i.e., in case mothers who were in STW in 2021 re-enter regular employment on a part-time basis).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Combined with the growing pressure for intensive parenting (Hays, 1996 ), this results in significant childcare investment by mothers. Although crises may potentially be a turning point that offer an opportunity for a different interpretation of existing gender arrangements within the family, studies show that during COVID-19 gender inequality has only been exacerbated, increasing the time women devote to domestic tasks (Chamorro-Premuzik & Ibarra, 2020 ; Craig & Churchill, 2020 ; Hank & Steinbach, 2021 ; Yaish et al, 2021 ).…”
Section: Work-family and The Gendered Division Of Labor At Homementioning
confidence: 99%
“…Most of the family members will be in the same household and upon doing these reviews, conflicts within gender division are often mentioned in the studies. According to Yaish et. al.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, with gender division becoming unbalanced and one gender is more vulnerable for job losses and reduction in income, this has led to gender inequality or gaps (Hasan et. al., 2020;Berniell & Fernandez, 2021;Casele & Posel, 2021;Feng & Savani, 2020;Yaish et. al., 2021;Meyer et.…”
Section: Methodsmentioning
confidence: 99%